Doctor Honoris Causa of the Adam Mickiewicz University for Professor Brian C.J. Moore - SĘK, Aleksander (Archives of Acoustics, 2016)
On November 9th, a.d. 2015, Professor Brian Cecil Joseph Moore form Cambridge University (UK), received the title of Doctor Honoris Causa of Adam Mickiewicz University from the hands of His Magnificence, the Rector of the AMU. This magnificent celebration was the great festivity for the entire Adam Mickiewicz University in Poznań, and particularly joyful for the Faculty of Physics and the Institute of Acoustics. This prestigious distinction has been awarded to Professor Moore, the most distinguished representative of the hearing sciences in Europe and unquestioned global authority in psychophysiological acoustics. Professor BrianMoore is a great scholar with a broad, in-depth knowledge and extremely wide research interests in many areas that go far beyond the mainstream of his research. He is a physicist, an acoustician and a psychologist. His main scientific achievements are related to the broadly understood neuro-science, particularly with regard to the functioning of the human auditory system. Professor Brian Moore is also a model of a scientific leader and a master; an inspiring and sympathetic guide and mentor of young scientists, the founder of his own school of hearing sciences, which brings together many generations of students and colleagues around the world. Let me therefore be allowed to bring some of his characteristics and achievements.